Determinants of Quick Response Code Indonesian Standard Usage Intention among Micro, Small, and Medium Enterprises in Paal Merah District - Nurafni Mardiana; Ahmad Syahrizal; Nova Erliyana (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: This study examines the influence of ease of use, security, and perceived benefits on the intention to use the Quick Response Code Indonesian Standard (QRIS) among micro, small, and medium enterprise (MSME) actors in Paal Merah District, Jambi City. The study responds to the limited empirical evidence on QRIS adoption at the district-level MSME context and contributes to the application of the Technology Acceptance Model in local digital payment behavior. Methodology: This study used a quantitative survey approach. Data were collected through questionnaires distributed to 100 MSME actors selected using purposive sampling. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, partial t-test, simultaneous F-test, and coefficient of determination with IBM SPSS Statistics 25. Findings: The results show that ease of use and perceived benefits have a positive and significant effect on QRIS usage intention, while security does not have a significant partial effect. Simultaneously, ease of use, security, and perceived benefits significantly influence QRIS usage intention. The adjusted R-square value of 0.695 indicates that the three variables explain 69.5% of the variation in usage intention.